STUDY OF Bacillus licheniformis BACTERIA AS A BIO-CONTROL AGENT IN REDUCING AFLATOXIN B1 TOXICITY IN DRIED GRAPE SAMPLES - H. Z. Hussein; E. K. Abdul-Karim; M. I. Alghannoum (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to isolate and identify fungi contaminating raisin samples and evaluate the effectiveness of bacteria in inhibiting fungal growth and reducing toxin levels. The isolation results the fungus A. flavus was the most frequent and appeared in the samples, reaching 54.5 and 44.4%, respectively. The results showed that all isolates of A. flavus had the ability to produce aflatoxin B1, as confirmed by the ammonia vapor test. The isolate with the highest toxin production was identified through nucleotide sequences deposited in the World Genomic Organization’s Gene Bank under accession number OR192858. The results demonstrated the ability of the live bacteria Bacillus licheniformis to inhibit fungal growth, reaching 94.4%, compared to 72.56% for the killed bacterial filtrate. The toxin concentration was 62.11 ppb in the toxin-producing isolate treated with bacteria, while it was 285.866 ppb in the toxin-producing isolate without bacteria. An 85.65% reduction in toxin levels was observed compared to the control, which registered 0%, with a toxin concentration of 41.08 ppb in the bacteria-treated toxin-producing isolate, while it was 285.866 ppb in the untreated toxin-producing isolate.